The Relationship Between Mothers' Knowledge And Social Support And Preventing Cigarette Smoke Exposure At Home In Smoke-Free Villages (SFV) - Alfi Fadillah; Anisa Catur Wijayanti (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Exposure to secondhand smoke in the home is still a public health problem that harms non-smokers, but is often overlooked. Although the City of Surakarta has implemented the Smoke-Free Village (Kampung Bebas Asap Rokok/ KBAR) program to encourage a smoke-free environment, the practice of smoke-free houses at the family level is not optimal. Mothers have an important role in preventing exposure to secondhand smoke such as implementing rules, supervision and support so that family members do not smoke in the house. Research Objective: To analyze the relationship between knowledge and social support in mothers with the prevention of exposure to cigarette smoke at home in the area of Smoke-Free Village (KBAR), Karangasem Village, Surakarta City. Methods: This type of research is quantitative analysis with a cross-sectional approach. The total sample was 96 respondents with a sampling technique using purposive sampling. Results: Data analysis using the Chi Square Test showed that there was a relationship between knowledge (p-value 0.001) and social support of mothers (p – value 0.001) and the prevention of exposure to cigarette smoke at home in the Smoke-Free Village (KBAR) area of Karangasem Village. Conclusions: Prevention behaviors of exposure to secondhand smoke at home are influenced by the level of knowledge and social support that mothers receive. Some do not understand exposure to second-hand smoke and lack emotional support from neighbors and community leaders. Therefore, it is necessary to strengthen education regarding exposure to indirect cigarette smoke (third-hand smoke), especially not to smoke in the house and maintain smokers' personal hygiene after smoking. The education must be directed at strengthening emotional support involving community leaders and the social environment to increase joint commitment in preventing exposure to cigarette smoke at home.